Phytogenetic Relationships of Mystacoleucus marginatus (Valenciennes 1842) based on Cytochrome Oxidase C Subunit I (COI) Gene - Fitri Sil Valen; Maheno Sri Widodo; Yuni Kilawati; R. Adharyan Islamy (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2019)
Mystacoleucus marginatus is a type of freshwater fish that is spread in various countries with tropical climates, one of which is Indonesia. This fish can be found in the Brantas River Basin (DAS), East Java. In its development, identification of fish species needs to be done in detail and more deeply, so that the correct identification results can be obtained. This study aims to identify genetic and phylogenetic characteristics of Mystacoleucus marginatus in the Brantas River Basin based on the Cytochrome Oxidase C Subunit I (COI) gene. Test samples were taken from 11 individuals of Mystacoleucus marginatus in the Brantas watershed, from June to August 2018. The results showed that Mystacoleucus marginatus in the Brantas watershed had 2 Haplotypes with Haplotype (Hd)=0.96 diversity values and nucleotides diversity (Pi)=0.00357. These results indicate that the population in the Brantas watershed is interconnected between one location and another sampling location, this is supported by a phylogenetic topology of DNA barcodes showing a monophyletic clade, as well as a haplotype distribution indicating that the sample area is genetics are not isolated from one another. So that the type of Mystacoleucus marginatus scattered along the Brantas watershed is still in one species, which is indicated by the low level of genetic variation. Genetic identification efforts must be carried out continuously so that appropriate information can be obtained for the diversity of fish species, especially endemic fish.